KEMAMPUAN MEMBACA AL-QUR'AN BAGISISWA SMP DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Ramlah Hakim (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Bone, South Sulawesi, especially atSMPN 1, SMPN 4, and SMPN 5 Bone. This research aims to describethe student ability on reading ATQur'an and factors influence thatability. This uses quantitative method, where data was collected byquestioner. Then, data was analyzed by statistical analysis.This research indicates that ability degree on reading Al-Qur'an ofthose students is commonly good enough. Their mean scores are 80.7 to86.9. SMPN 5 get the highest score (86.9), SMPN 1 get the middle score(86.4), and SMPN 4 get the lowest score (80.7). The factor that significantlyinfluence that students ability is the method in reading (andwriting) Al-Qur'an.